Ordinary dogs, extraordinary friendships : stories of loyalty, courage, and compassion - Flowers, Pam (Alaska Northwest Books, 2013)
Collects eleven stories that showcase dogs exemplifying positive character traits such as wisdom, loyalty, courage, and good judgment.